Accessibility and Willingness of Patients to Pay for Pharmaceutical Care Services in a Tertiary Health Facility, Benin City, Nigeria - Osarenmwinda, Monday Ikponmwosa; Eze, John Nonso (Journal of Pharmacy Practice and Community Medicine, 2026)
Background: Understanding cost and other barriers to Pharmaceutical Care Services (PCS) delivery in Nigeria is key to improving practice and informed government resource allocation. Objectives: This study identifies barriers, perceived value of, and willingness to pay for PCS at University of Benin Teaching Hospital UBTH, Benin City. Materials and Methods: A cross-sectional study was conducted among 311 patients who visited the General Practice Clinic (GPC) pharmacy unit of UBTH. Data were analyzed using SPSS version 23. Descriptive and inferential statistics were applied, with significance set at p<0.05. Results: Most respondents (63%) considered pharmacist-led medication reviews very important, and 65.9% believed pharmacists could significantly improve their health outcomes. Over half (65.3%) of the respondents were willing to receive PCS virtually. The overall satisfaction score was moderate (mean=3.41±1.07). Financial considerations influenced uptake, with 46.9% willing to pay between ₦500-₦2000 ($0.35 to $1.38) per consultation. Employment status, age, and household income significantly influenced perceived value and willingness to pay (p<0.05). Higher education and income levels were associated with greater willingness to pay for PCS. Conclusion: The study highlights a strong recognition of the value of pharmaceutical care services among patients, but cost and limited pharmacist availability hinder access; telepharmacy and flexible payments may improve uptake.
Keywords: Accessibility; Nigeria; Patient satisfaction; Pharmaceutical care services; Telepharmacy; Willingness to pay